Advanced manufacturing systems : selected, peer reviewed papers from the 2011 International Conference on Materials and Products Manufacturing Technology (ICMPMT 2011), October 28-30, 2011, Chengdu, China - Ai, Zhijiu (Advanced materials research, 2011)
These papers, subjected to peer-review by expert referees, describe the latest advances in, and applications of, measurement control technologies and intelligent systems, transmission and control of fluids, embedded systems, NEMS/MEMS technology and equipment, monitoring and control of manufacturing processes, petroleum machinery and engineering and other related topics. Review from Book News Inc.: Participants from industry and academia present about 150 papers on measure control technologies and intelligent systems, transmitting and controlling fluid, embedded systems, technology and equipme.